Envolvimento da enzima naphoxidase no efeito nefroprotetor do (-)-α-Bisabolol em um modelo de lesão renal aguda por isquemia-reperfusão In vitro - Sampaio, Tiago Lima (2018)
Acute Renal Injury (AKI) is associated with high morbidity and mortality, generating public health costs. Ischemia and reperfusion (I/R) are events that frequently lead to AKI due to tissue hypoxia, reactive oxygen species (ROS) production, oxidative stress and programmed cell death by apoptosis. Previously, we have demonstrated the nephroprotective potential of (-)-α-Bisabolol, an unsaturated monocyclic sesquiterpene of chamomile flowers. The objective of the present study was to evaluate the mechanism of nephroprotection mediated by Bisabolol in human tubular renal cells after induction of I/R in an in vitro model. Additionally, this work intends to analyze the involvement of ROS generated by NOX4 in the lesion and cellular recovery. HK2 cells were exposed to I/R conditions and treated with Bisabolol at various concentrations. Cell viability was performed by the MTT assay. Treated and untreated cells were submitted to flow cytometry to evaluate necrotic/apoptotic cells, ROS production and mitochondrial transmembrane potential. TBARS and GSH were used as redox balance parameters. In addition, the levels of KIM-1 released in the supernatant were measured by ELISA. In order to identify an interaction between Bisabolol and NOX4, molecular docking and enzymatic assays in vitro were performed. Expression of the NOX4 isoform in treated cells was assessed by Western blotting. Finally, the cells were visualized by scanning electron microscopy. Bisabolol improved cell viability and prevented cell death by apoptosis, also indicated by decreased levels of KIM-1 in the cell supernatant. A decrease in ROS production and mitochondrial depolarization was observed, with antioxidant regulation by the increase of GSH and decrease of lipid peroxidation. It has also been shown that treatment with Bisabolol can inhibit NOX4. Scanning electron microscopy images showed that Bisabolol reduced cell injury induced by I/R. Therefore, treatment with Bisabolol protects renal tubular epithelial HK2 cells against the oxidative damage caused by I/R. This effect is related to inhibition of apoptosis, decreased release of KIM-1, and establishment of REDOX balance through inhibition of NOX4 activity in tubular cells.